Understanding and Managing Sepsis in Patients With Cancer in the Era of Antimicrobial Resistance - Gudiol, Carlota; Albasanz-Puig, Adaia; Cuervo, Guillermo; Carratalà, Jordi (Frontiers in Medicine, 2021)
Sepsis is a frequent complication in immunosuppressed cancer patients and hematopoietic stem cell transplant recipients that is associated with high morbidity and mortality rates. The worldwide emergence of antimicrobial resistance is of special concern in this population because any delay in starting adequate empirical antibiotic therapy can lead to poor outcomes. In this review, we aim to address: 1) the mechanisms involved in the development of sepsis and septic shock in these patients; 2) the risk factors associated with a worse prognosis; 3) the impact of adequate initial empirical antibiotic therapy given the current era of widespread antimicrobial resistance; and 4) the optimal management of sepsis, including adequate and early source control of infection, optimized antibiotic use based on the pharmacokinetic and pharmacodynamics changes in these patients, and the role of the new available antibiotics.